(untitled) (Ukrainian Journal of Physics, 2026)
“New Trends in High-Energy Physics” is a series of scientific conferences initiated by the Bogolyubov Institute for Theoretical Physics of the National Academy of Sciences of Ukraine in 1992. The conferences are devoted to topical problems in experimental and theoretical physics, nuclear and particle physics, astrophysics, high-energy physics, and physics beyond the Standard Model.